Magnetically separable Fe3O4-SiO2/Pt catalyst and its application for uranium reduction - Kuntal Kumar Pal; Ramakrishna Reddy; Chanchal Ghosh; K. Ananthasivan; P. Velavendan; Ramesh L. Gardas; Sandip Dhara (Scientific Reports)
Abstract Magnetically separable Fe3O4-SiO2/Pt catalysts with ~ 2% Pt loading have been developed for the generation of U(IV) in HNO3-N2H4 medium, used in the nuclear spent fuel reprocessing. Pt was impregnated in the catalysts via reductive heat treatment. The catalysts were characterized by x-ray diffraction, magnetization measurement, field emission scanning electron microscope and high-resolution transmission electron microscope studies. Catalysts reduced at 200 °C and above temperatures were found to be sufficient for the complete reduction of Pt to its Pt(0) state and were highly efficient for the U(IV) generation via hydrogenation. The U(IV) produced during the experiment was analyzed via the titrimetric and spectroscopic methods. Among all the catalysts prepared under the scope of the study, the highest saturation magnetization was measured for the Fe3O4-10SiO2/Pt catalysts prepared at 200 °C (Fe3O4-10SiO2/Pt(200)). However, the catalyst was least effective towards U(VI) reduction compare to the catalysts prepare at 250 °C (Fe3O4-10SiO2/Pt(250)) and 300 °C (Fe3O4-10SiO2/Pt(300)). The saturation magnetization of Fe3O4-10SiO2/Pt(300) was found to be higher than that of Fe3O4-10SiO2/Pt(250). Finally, Fe3O4-10SiO2/Pt(300) was considered a model catalyst for the detailed characterization, benchmarking and recycling of the catalyst material. Samples with higher silica content were also prepared at 300 °C and assessed for their catalytic activity.